DIAMETER OPTIMIZATION IN MULTIPHASE PIPELINE NETWORK - Ristiyan Ragil Putradianto; Silvya Dewi Rahmawati (PETRO: Jurnal Ilmiah Teknik Perminyakan, 2020)
Optimization is a continuous work in oil and gas operation in every section by maximizing the profit and minimizing cost. One of the sections that can be optimized is production system, starting from the wellbore to separator through pipeline network. Simulation are made and conducted from reservoir to separator to see the pressure distribution along the pipeline with various diameter. The result will be subject to be optimized by putting pipeline cost into account. The simulation result shows that at some point, increasing in diameter has a good effect to the revenue thanks to the increasing production rate, but it also shows that the increasing diameter in all section is not always the best scenario due to high cost. Benefit-to-cost ratio is chosen to be the economical parameter to find the best diameter configuration.